Increasing Student Creativity Through The Implementation Of Dance Learning In Special Schools (SLB) - Selfiana Saenal (Universitas Muhammadiyah Enrekang, 2023)
Abstrak Dance training in schools is one of the basics of learning in cultivating the talent and capacity of stunt actors, and dance learning is very important, considering that dance learning underlines the course of training in developing character which includes coaches and stunt performers and can build the imagination of stunt development for children. normal children as well as for children who have physical or mental disabilities who meet the requirements for dance learning. The aim of this research is to examine the creative dance movements of blind students who use the storytelling learning model in dance learning, as well as the process of incorporating this model into dance learning. This research uses a subjective methodology using fascinating investigative techniques. The subjects in this review were 2 people, namely fourth grade students, the school principal, and the homeroom teacher. Observation, interviews, tests, and documentation are data collection methods. The findings of this research are as follows: the narrative learning model with increased narration in dance learning is very useful in creating dance development imaginations for blind students in the dance experience. The ability of blind stunt performers to obtain data using only the sense of hearing with enhanced narration makes perfect sense to be applied to blind stunt performers, the most common way of implementing the narrative learning model in dance learning can be said to be good because stunt performers do not experience obstacles in the dance experience. and the consequences of using a narrative learning model in dance learning on the development of imagination can be expected to be strong, considering that the imagination of dance development in blind stunt actors develops from the emotional, mental, psychomotor and mental parts.Kata Kunci: Tari, Disabilitas, Sekolah Luar BiasaAbstractDance training in schools is one of the basics of learning in cultivating the talent and capacity of stunt actors, and dance learning is very important, considering that dance learning underlines the course of training in developing character which includes coaches and stunt performers and can build the imagination of stunt development for children. normal children as well as for children who have physical or mental disabilities who meet the requirements for dance learning. The aim of this research is to examine the creative dance movements of blind students who use the storytelling learning model in dance learning, as well as the process of incorporating this model into dance learning. This research uses a subjective methodology using fascinating investigative techniques. The subjects in this review were 2 people, namely fourth grade students, the school principal, and the homeroom teacher. Observation, interviews, tests, and documentation are data collection methods. The findings of this research are as follows: the narrative learning model with increased narration in dance learning is very useful in creating dance development imaginations for blind students in the dance experience. The ability of blind stunt performers to obtain data using only the sense of hearing with enhanced narration makes perfect sense to be applied to blind stunt performers, the most common way of implementing the narrative learning model in dance learning can be said to be good because stunt performers do not experience obstacles in the dance experience. and the consequences of using a narrative learning model in dance learning on the development of imagination can be expected to be strong, considering that the imagination of dance development in blind stunt actors develops from the emotional, mental, psychomotor and mental parts.Keywords : Dance, Disability, Special Schools